Prevalensi Dan Faktor-Faktor Penyebab Musculoskeletal Disorders Pada Operator Gudang Industri Ban PT X Tangerang Indonesia - Revadi, Chindy Elsanna; Gunawan, Cahya Surya; Rakasiwi, Galih Jaler (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2019)
Musculoskeletal disorders which are an injury or pain in the human musculoskeletal system can reduce productivity especially the warehouse workers at a tire industry.  This research aims to observe the prevalence and the factors which increase the musculoskeletal disorders among the warehouse workers at a tire industry.  Thirty warehouse workers of a tire warehouse participated in this study by filling out a Nordic Body Map questionnaire or skeletal muscle complaints instrument. The result of this study showed that the highest prevalence of the musculoskeletal disorders at the warehouse workers at a tire industry occurred at the lower back area. The factors which influence the risk of musculoskeletal disorders of the warehouse workers at the tire industry are age, weight, educational background, and the duration of working by using the lower back, knees, and ankles. To reduce the risk of musculoskeletal disorders, it is necessary to supervise the work posture and design a work environment which involves all members of the company .